Domestic wastewater treatment using multi-layer constructed wetlands: an overview - Jais, N. M.; Mohamed, R. M. S. R; Fauzi, M. S. M; Al-Gheethi, A.A.S (Penerbit UTHM, 2020)
Domestic wastewater is generated from residential, institutional, commercial, and industrial establishments is disposed of via drainage and sewers. Usually, the wastewater is not treated from the primary sewage treatment and gets discharged to drainage without initial treatment. Thus, it is necessary to create an environmentally-friendly method to reduce any pollution issues. This chapter provides insights into overview from previous studies about characteristics of domestic wastewater, results of the treatments using the multi-layer constructed wetlands, type of plants for vegetation wetlands, and parameters needed for the optimisation the multi-layer constructed wetlands. As the low-cost and affordable technology systems, the multi-layer constructed wetlands are the potential alternative to achieve the treatment efficiency.